Exploring Digital Native Consumers’ Purchase Intention in Airline Services using TAM: The Mediating Role of Trust - Didip Diandra; Endang Ruswanti; Zainur Hidayah; Ahmad Azmy (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to investigate and explore the digital native consumers’ purchase intention in airline services using Technology Acceptance Model (TAM). This study examined the direct and indirect effect of perceived usefulness, perceived ease of use, and trust on purchase intention within digital airline platforms. A quantitative research design was employed; data was collected through a structured online survey to 160 digital native respondents. Data were analyzed by SEM-PLS in SmartPLS 4. The result of analysis shows perceived ease of use and trust plays a strong and significant effect on purchase intention, while the direct influence of perceived usefulness on purchase intention is positive but not statistically significant. Both variables framework significantly enhance trust and mediate their effect on purchase intention. This study extended Technology Acceptance Model (TAM) to digital native consumers in the airline service context. Digital native consumers evaluate technology differently from earlier generations; thus, providers and policy makers must pay attention to it. This research offers insights into how perceived ease of use and trust shape online purchase decision.